Exhibition of normal distribution in finite p-groups (2017)
Suppose that G is a group of order m p and n ≤ m. Let Sn(G) be the number of subgroups of order p n in G. Then, the number of subgroups of order pn is normally distributed with respect to n, where n is a positive integer.